Diabetes IN hospital – Glucose and Outcomes in the COVID‐19 pandemic (DINGO COVID‐19): the 2020 Melbourne hospital experience prior to novel variants and vaccinations. Issue 1 (21st October 2022) - Barmanray, Rahul D.; Gong, Joanna Y.; Kyi, Mervyn; Kevat, Dev; Islam, Mohammad A.; Galligan, Anna; Manos, Georgina R.; Nair, Indu V.; Perera, Nayomi; Adams, Nicholas K.; Nursing, Ashvin; Warren, Annabelle M.; et al.
Abstract: Background and Aims: A relationship between diabetes, glucose and COVID‐19 outcomes has been reported in international cohorts. This study aimed to assess the relationship between diabetes, hyperglycaemia and patient outcomes in those hospitalised with COVID‐19 during the first year of the Victorian pandemic prior to novel variants and vaccinations. Design, setting: Retrospective cohort study from March to November 2020 across five public health services in Melbourne, Australia. Participants: All consecutive adult patients admitted to acute wards of participating institutions during the study period with a diagnosis of COVID‐19, comprising a large proportion of patients from residential care facilities and following dexamethasone becoming standard‐of‐care. Admissions in patients without known diabetes and without inpatient glucose testing were excluded. Results: The DINGO COVID‐19 cohort comprised 840 admissions. In 438 admissions (52%), there was no known diabetes or in‐hospital hyperglycaemia, in 298 (35%) patients had known diabetes, and in 104 (12%) patients had hyperglycaemia without known diabetes. ICU admission was more common in those with diabetes (20%) and hyperglycaemia without diabetes (49%) than those with neither (11%, P < 0.001 for all comparisons). Mortality was higher in those with diabetes (24%) than those without diabetes or hyperglycaemia (16%, P = 0.02) but no difference between those with in‐hospital hyperglycaemia and either of the other groups. On multivariable analysis, hyperglycaemia was associated with increased ICU admission (adjusted odds ratio (aOR) 6.7, 95% confidence interval (95% CI) 4.0–12, P < 0.001) and longer length of stay (aOR 173, 95% CI 11–2793, P < 0.001), while diabetes was associated with reduced ICU admission (aOR 0.55, 95% CI 0.33–0.94, P = 0.03). Neither diabetes nor hyperglycaemia was independently associated with in‐hospital mortality. Conclusions: During the first year of the COVID‐19 pandemic, in‐hospital hyperglycaemia and known diabetes were not associated with in‐hospital mortality, contrasting with published international experiences. This likely mainly relates to hyperglycaemia indicating receipt of mortality‐reducing dexamethasone therapy. These differences in published experiences underscore the importance of understanding population and clinical treatment factors affecting glycaemia and COVID‐19 morbidity within both local and global contexts.